The Influence of Economic Growth, Inter-Regional Disparities and Absorbed Labor on Welfare - Ulfia Rachmah; Dita Fadhila; Ropini Amelia; Maya Panorama (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2023)
ABSTRACT The final manifestation of improving welfare will be reflected in increasing income, reducing disparities between regions, improving people's quality of life so that the level of the economy can grow. Improvements in people's welfare can be realized through a number of development programs. The aim of thyis research was to examine how much economic growth, labor absorption and disparities between regions affect welfare in the districts/cities of South Sumatra from 2016-2022. This paper uses 3 X variables against 1 Y variable in the Regency/City of South Sumatra Province with a time series of 7 years. The research method is explanatory research with quantitative methods. The population in this research is data on time intervals for all variable. The techniques to collecting the data are saturated sampling from statistical publications, periodicals, volumes, documents and scientific collections. The samples in this research are data from 2016 to 2022, is 17 samples obtained from quarterly data for 9 years. Research uses secondary data. These include a time series from 2016 to 2022 and a cross-selection series covering 17 districts/cities. The techniques of data analysis are the Classical Assumption Test, Inferential Statistical Analysis (Linear Relation Analysis, T Test, F Test, R2). The results of the research in the partial test are that economic growth and absorbed labor do not have a significant effect on welfare. Inequality between regions has a significant negative effect on welfare. And in the Simultaneous Test all X variables have a simultaneous effect on welfare.Keywords: Economic growth, absorbed workforce, disparities between                     regions, welfare.